Blood Biomarkers for Amyotrophic Lateral Sclerosis: Myth or Reality?. (2nd June 2014) - Robelin, Laura; Gonzalez De Aguilar, Jose Luis
Abstract : Amyotrophic lateral sclerosis (ALS) is a fatal condition primarily characterized by the selective loss of upper and lower motor neurons. At present, the diagnosis and monitoring of ALS is based on clinical examination, electrophysiological findings, medical history, and exclusion of confounding disorders. There is therefore an undeniable need for molecular biomarkers that could give reliable information on the onset and progression of ALS in clinical practice and therapeutic trials. From a practical point of view, blood offers a series of advantages, including easy handling and multiple testing at a low cost, that make it an ideal source of biomarkers. In this review, we revisited the findings of many studies that investigated the presence of systemic changes at the molecular and cellular level in patients with ALS. The results of these studies reflect the diversity in the pathological mechanisms contributing to disease (e.g., excitotoxicity, oxidative stress, neuroinflammation, metabolic dysfunction, and neurodegeneration, among others) and provide relatively successful evidence of the usefulness of a wide-ranging panel of molecules as potential biomarkers. More studies, hopefully internationally coordinated, would be needed, however, to translate the application of these biomarkers into benefit for patients.